Stopnja anksioznosti in različne strategije spoprijemanja s stresom pri vojakih Slovenske vojske - Dolenc, Petra (Zdravstveno varstvo, 2009)
Objective: The aim of the study was to determine the anxiety level, self-regulation and stress-coping strategies of the Slovenian Armed Force''s members, and to examine differences between the psychological variables measured in the selected occupational groups. Methods: We studied 59 male soldiers showing different competencies and performing different duties. All participants completed the Trait Anxiety Scale, the Self-Regulation Scale and the Ways of Coping Questionnaire. Results: The participating soldiers showed low anxiety levels, high self-regulation and a tendency to cope actively with problem situations. We idenitfied, however, significant differences in some ofthe measured variables between military candidates, on the one hand, and other professional groups of the Slovenian Armed Forces, on the other. Conclusion: This issue deserves special attention and consideration in the future. It would be reasonable to identify the relationship between certain psychological aspects and motor skills and work efficiency of Slovenian soldiers.
Keywords: anksioznost; poklicni stres; samoregulacija; stres; vojaki